Civil engineers' role in saving the world: updating the moral basis of the profession. Issue 5 (5th March 2021) - Francis, Nick
Abstract : Today's civil engineering profession was born in the industrial revolution with the vision of 'harnessing the forces of nature for the benefit of mankind'. However, the industry's alarming environmental impact means that civil engineers must urgently change their impact on the world. Viewing the dangers of climate change through the lens of behavioural science, this paper identifies the four 'levers' that civil engineers must pull to put the profession on a sustainable and morally justifiable path. Three of the levers focus on behaviours, outlining measures that individuals, companies and institutions can take to realign decision making to the needs of sustaining life on the planet. Only one lever relates to new technological solutions. These levers offer a pragmatic to-do list of actions, to unlock systemic change, and thereby accelerate the profession's transition to a net-zero future.